Hedging effectiveness of US soybean oil futures - Lee, Jia Wei (2023)
This paper study the hedging effectiveness of US Soybean oil Futures. Soybean oil was the most consumable vegetable oil in the world and the United State was the largest soybean oil exporter. Besides, the commodity market was highly impacted by the recent pandemic and the Russia-Ukraine war which might have affected the hedging effectiveness. At the same time, this paper will also examine the price volatility before and after the pandemic and the Russia-Ukraine war. The spot and futures prices for US soybean oil are used in this paper, on a daily frequency from 1st May 2012 to 30th June 2022 which is approximate a 10-year data. The data will be split into three sub-period comprised of the pre-Covid period starting from 1st May 2012 to 10th March 2020, the Covid period starting from 11th March 2020 to 23rd February 2022, and the Russia-Ukraine war period starting from 24th February 2022 to 30th June 2022. This study employed the OLS, B-VAR, B-VEC, DVEC M-GARCH, and CCC M-GARCH to compute the optimal hedge ratio. Besides, this paper also utilizes the GARCH (1,1) model for price volatility. The findings show that the hedging effectiveness during the pre-Covid period was higher than Covid and Russia-Ukraine war period as in its underlying spot position a greater percentage of risk reduction was realized. However, the result from the multivariate GARCH model has a lower risk reduction percentage than the constant hedge ratio during the pandemic and the Russia-Ukraine war which is opposed to the previous literature. This is because most of the literature concludes that the dynamic hedge model provides a greater hedge ratio than constant hedge models such as Park and Switzer.